Examining the impact of Advanced Work Packaging and WorkFace planning on direct work rates of on-site construction workers: a comparative analysis - Porwal, Vishal; O’Brien, William J.; Borcherding, John D. (Frontiers in Built Environment, 2025)
Efficiency in on-site construction has long been a pursuit for project stakeholders, with a focus on enhancing direct-work rates—the time spent by craft workers on installation activities. However, despite the promising potential of methodologies such as Advanced Work Packaging (AWP) and WorkFace Planning (WFP) in being associated with enhancing these rates, there is limited officially published evidence, with much of the available data derived from narrow datasets. This study addresses this research gap by investigating the impact of AWP and WFP implementation on direct-work rates using two distinct datasets spanning from 2015 to 2023. The first dataset comprises 61 projects from a productivity consultant, while the second dataset consists of 23 projects sourced from a large engineering, procurement, and construction (EPC) firm, covering a diverse range of global projects. The findings indicate that projects employing AWP and WFP are correlated with significantly higher direct-work rates and demonstrate improved predictability of direct-work rates compared to those that do not implement these methodologies. This study contributes to the body of knowledge by emphasizing the value of AWP and, more broadly, the significance of systemic management interventions in both front-end and on-site planning. In addition to the specific findings about AWP and WFP, this paper also demonstrates probability-based methods to assess predictability from work sampling data, a novel application for exploring construction productivity.